Qualitatife Test of Papaya Leaves, Cassava Leaves, and Melinjo Leaves as Alternative Ingredients for Foods Rich in Vitamin C for the Community - Susanti, Ariska Septiyani; Rahayu, Rina (Universitas Negeri Semarang, 2021)
One of the roles of vitamin C in the body is as an antioxidant compound that can counteract free radicals, besides that vitamin C also acts as an immunomodulator that stimulates neutrophil migration, forms oxidants, kills microbes and increases phagocytosis. In addition, vitamin C can reduce the risk of complications in patients who have been exposed to COVID-19, reduce the risk of contracting it, prevent symptoms from appearing and can increase the body's resistance or immunity. The purpose of this study was to determine the presence of vitamin C in papaya leaves (Carica papaya), cassava leaves (Manihot Esculenta), and melinjo leaves (Gnetum gnemon) which can be used as alternative foods rich in vitamin C for the community. This research was conducted with a qualitative method. From the results of observations, the three samples showed positive results for vitamin C. With the results of this study, it is hoped that it can be used as an alternative food ingredient for the community to meet their daily vitamin C needs, especially during the Covid-19 Pandemic like now vitamin C is needed to increase the body's resistance so that it does not susceptible to various diseases.